Toxicological studies of the combined effects of aluminium, copper and manganese on a freshwater amphipod in acidic waters - Musibono, Diudonné-Athanase Eyul'anki-Ekwalang'Ayor (Department of Biological Sciences, 2016)
This thesis describes the combined toxicity in aqueous solutions of three common metals (Al, Cu and Mn) on the endemic freshwater amphipod Paramelita nigroculos (Barnard) from the south-western Cape region of South Africa. The aims of the work were three-fold: to examine the toxic effects of combinations of the three metals; to investigate such effects on an indigenous aquatic organism; and, to investigate eh adequacy of the South African "Guidelines for aquatic ecosystems", which are derived from the data based on the effects of individual elements.